Pembrolizumab Combined With Neoadjuvant Chemotherapy Versus Neoadjuvant Chemoradiotherapy Followed by Surgery for Locally Advanced Oesophageal Squamous Cell Carcinoma: Protocol for a Multicentre, Prospective, Randomized-Controlled, Phase III Clinical Study (Keystone-002) - Shang, Xiaobin; Zhang, Wencheng; Zhao, Gang; Liang, Fei; Zhang, Chen; Yue, Jie; Duan, Xiaofeng; Ma, Zhao; Chen, Chuangui; Pang, Qingsong; Zhang, Weihong; Liu, Liang; et al. (Frontiers in Oncology, 2022)
Background To compare the efficacy and safety of pembrolizumab combined with neoadjuvant chemotherapy (neoCT) versus neoadjuvant chemoradiotherapy (neoCRT) followed by surgery for locally advanced resectable oesophageal squamous cell carcinoma (ESCC). Methods This study is a multicentre, prospective, randomized-controlled, phase III clinical study. Eligible ESCC (staging: cT1N2M0 or cT2-3N0-2M0 (stage II/III, high-risk lesions in T2N0M0)) patients will be randomly assigned to either the experimental group (pembrolizumab with neoCT, n = 228) or the control group (neoCRT, n = 114) at a ratio of 2:1. Within 4–6 weeks after preoperative therapy, the McKeown procedure will be performed. Patients in the experimental group will also receive pembrolizumab alone as adjuvant therapy after surgery until 1 year or until the radiographically confirmed PD or other condition indicated for premature termination is observed. The primary endpoint is event-free survival (EFS). The secondary endpoints are 1-, 3-, and 5-year overall survival (OS) and disease-free survival (DFS), short-term outcomes, and quality of life. Discussion This is the first prospectively randomized controlled trial designed to compare pembrolizumab plus chemotherapy and chemoradiotherapy as neoadjuvant therapy for resectable ESCC. According to our hypothesis, preoperative pembrolizumab combined with chemotherapy will result in a better tumour response and prolong the survival of patients, with acceptable toxicity. This study started in December 2021, and the enrolment time is estimated to be 2 years. Trial Registration This prospective study has been registered at ClinicalTrials.gov (NCT04807673), March 2021.